2012
DOI: 10.1007/s12291-012-0276-x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Correlates with Complications Among Diabetic Patients Attending a Diabetic Clinic in Muhimbili National Hospital, Dar es Salaam, Tanzania

Abstract: In diabetes, persistent hyperglycemia results in increased production of free radicals especially oxygen free radicals, which can cause cell destruction and tissue injury resulting in cell dysfunction. With the premise that oxidative stress is a major cause of diabetic complications, we conducted a controlled laboratory based investigation on level of lipid peroxide levels in the serum of Type 1 and Type 2 diabetic patients attending Muhimbili National Hospital. From our clinical data it was observed that majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Considering these variants, Kimura et al [61] identified increased levels of EC-SOD in T2DM carriers, especially in the presence of micro and macrovascular complications. On the other hand, diminished SOD activity was also observed in such individuals [63,73,75,78]. As for glutathione peroxidase (GPx) and catalase (CAT) enzymes, Colak et al [75] detected reduced activity for both in patients with T2DM presenting with complications, whereas Kasznick et al [63] observed diminishment for GPx activity in T2DM carriers presenting with neuropathy, while Moemen et al observed a decrease in the activity of GPx in diabetic patients with proliferative neuropathy (PDR) [74].…”
Section: Main Biomarkers Evaluated In the Clinical Studies Presentedmentioning
confidence: 99%
“…Considering these variants, Kimura et al [61] identified increased levels of EC-SOD in T2DM carriers, especially in the presence of micro and macrovascular complications. On the other hand, diminished SOD activity was also observed in such individuals [63,73,75,78]. As for glutathione peroxidase (GPx) and catalase (CAT) enzymes, Colak et al [75] detected reduced activity for both in patients with T2DM presenting with complications, whereas Kasznick et al [63] observed diminishment for GPx activity in T2DM carriers presenting with neuropathy, while Moemen et al observed a decrease in the activity of GPx in diabetic patients with proliferative neuropathy (PDR) [74].…”
Section: Main Biomarkers Evaluated In the Clinical Studies Presentedmentioning
confidence: 99%